European Respiratory Society statement on thoracic ultrasound. Issue 3 (4th March 2021) - Laursen, Christian B.; Clive, Amelia; Hallifax, Rob; Pietersen, Pia Iben; Asciak, Rachelle; Davidsen, Jesper Rømhild; Bhatnagar, Rahul; Bedawi, Eihab O.; Jacobsen, Niels; Coleman, Courtney; Edey, Anthony; Via, Gabriele; et al.
Thoracic ultrasound is increasingly considered to be an essential tool for the pulmonologist. It is used in diverse clinical scenarios, including as an adjunct to clinical decision making for diagnosis, a real-time guide to procedures and a predictor or measurement of treatment response. The aim of this European Respiratory Society task force was to produce a statement on thoracic ultrasound for pulmonologists using thoracic ultrasound within the field of respiratory medicine. The multidisciplinary panel performed a review of the literature, addressing major areas of thoracic ultrasound practice and application. The selected major areas include equipment and technique, assessment of the chest wall, parietal pleura, pleural effusion, pneumothorax, interstitial syndrome, lung consolidation, diaphragm assessment, intervention guidance, training and the patient perspective. Despite the growing evidence supporting the use of thoracic ultrasound, the published literature still contains a paucity of data in some important fields. Key research questions for each of the major areas were identified, which serve to facilitate future multicentre collaborations and research to further consolidate an evidence-based use of thoracic ultrasound, for the benefit of the many patients being exposed to clinicians using thoracic ultrasound. Continued clinical use and research has established thoracic ultrasound as a key tool and skill for the modern pulmonologist https://bit.ly/3cCL6KS